2023
DOI: 10.1371/journal.pone.0284976
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype based clustering, and diversity of common bean genotypes in seed iron concentration and cooking time

Abstract: Common bean is the world’s most important directly consumed legume food crop that is popular for calories, protein and micronutrients. It is a staple food in sub-Saharan Africa, and a significant source of iron for anemic people. However, several pests, soil and weather challenges still impede its production. Long cooking time, and high phytic acid and polyphenols that influence bioavailable iron also limit the health benefits. To inform population improvement strategies and selection decisions for resilient f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…93 Testing of samples from more genotypes and market classes on dynamic digestion platforms would further inform breeding efforts. In such studies, we would recommend incorporating an empirical evaluation of cooking time [94][95][96][97] and continued use of genotypespecific cooking times to maximize comparability of digestive outcomes across samples; the effects of environment on cooking time have been found to be less major. 95,98 These dynamic digestion platforms could also inform research and development efforts in other grain legumes.…”
Section: Operational Considerations and Recommendations For Use Of Dy...mentioning
confidence: 99%
“…93 Testing of samples from more genotypes and market classes on dynamic digestion platforms would further inform breeding efforts. In such studies, we would recommend incorporating an empirical evaluation of cooking time [94][95][96][97] and continued use of genotypespecific cooking times to maximize comparability of digestive outcomes across samples; the effects of environment on cooking time have been found to be less major. 95,98 These dynamic digestion platforms could also inform research and development efforts in other grain legumes.…”
Section: Operational Considerations and Recommendations For Use Of Dy...mentioning
confidence: 99%
“…These studies were conducted in different environments and used biparental populations, which revealed variation between the involved parents. Genome-wide association studies (GWAS), in which variation is captured among a defined population, have also reported genomic regions associated with seed size, shape, and quality traits (Blair et al 2009 ; Schmutz et al 2014 ; Cichy et al 2015 ; Moghaddam et al 2016 ; Giordani et al 2022 ; Amongi et al 2023 ). All of these genetic studies have described major, minor, and epistatic QTL for seed traits across all 11 common bean chromosomes (Arriagada et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in plant breeding and phenotyping contributed to elucidating physiological mechanisms related to the description of developmental stages, dry matter accumulation dynamics per organ, source-sink relationships, and plant growth simulation models [20,21], which are of great utility for selecting parents with traits of interest [14] in favor of improving the response of common beans to stress conditions [13,16]. One of the most important breeding traits for genetic enhancement is biofortification, which seeks to biologically increase Fe and Zn concentrations in the grain [22][23][24]. Results on screening of seeds of bean germplasm indicated an average concentration (mg kg −1 ) of Fe and Zn of 55 and 28, respectively, with extremes of 102 for Fe and 54 for Zn [25].…”
Section: Introductionmentioning
confidence: 99%